Density and phenology of the invasive mealybug Delottococcus aberiae on citrus: implications for integrated pest management - Martínez-Blay, Victoria; Pérez-Rodríguez, Jésica; Tena, Alejandro; Soto, Antonia (2019)
Delottococcus aberiae De Lotto (Hemiptera: Pseudococcidae) is a new invasive citrus pest in Spain. It causes severe fruit distortions and, as a new invasive mealybug, there is a lack of information about its biology. This research aims to examine the seasonal trend of D. aberiae in citrus, using several sampling methods, as a first step to develop an integrated pest management program. Ten citrus orchards from Eastern Spain were periodically sampled during three years using absolute (plant material) and relative (corrugated cardboard band traps and sticky traps) sampling methods. The three sampling methods showed that D. aberiae completes multiple generations per year, two of them being clearly defined and resulting in high populations. D. aberiae peaked between May and June, damaging the developing fruit. Corrugated cardboard band traps were able to detect prepupa and pupa male instars and gravid females, providing a quantitative measurement of D. aberiae density at its first population peak. The use of corrugated cardboard band traps is recommended to monitor population levels and sticky traps to determine male flight periods, representing simple sampling techniques to monitor D. aberiae. These results will improve the sampling protocols and allow for the development of an integrated pest management program.